Krieg gegen Frauen
This documentary focuses on the specific targetting of women since the outbreak of war in the former Yugoslavia in 1991. The film begins by tracing the history of rape during warfare, first citing examples from the Bible, then likening the plight of women in the Balkans to that of women in other historic wars such as WWI and WWII, including archival footage from Bangladesh, Afghanistan, Iraq, Germany, and Korea. Many testimonies are featured with women who endured rape and other maltreatment. Different members of the Bosnian community are interviewed about the effect of the war on women there, primarily Muslims. The documentation center in Zagreb is highlighted as well for its efforts to document the experience of refugees and record war crimes. Doctors are interviewed about abortion as a potential option and its effect on the women.